COMPARISON OF REGULATORY MODELS OF HIGHER EDUCATION IN EUROPE. THE PORTUGUESE SITUATION (Avaliação: Revista da Avaliação da Educação Superior, 2010)
The regulation of Portuguese Higher Education is now in a period of evolution and undergoing profound changes. The quality assurance system implemented was criticised from the beginning, raising many doubts, and was often associated with some weaknesses. The pressure put on the Portuguese government to meet quality assurance standards in the scope of European Higher Education is enormous and several reforms and policy developments show that Portugal’s Higher Education system is on the move. This paper compares the regulatory models in other European countries and analyses the new Portuguese model.